Winter and Summer Rossby Wave Sources in the CMIP5 Models - Yu Nie; Yang Zhang; Xiu‐Qun Yang; Hong‐Li Ren (Earth and Space Science, 2019)
Abstract The Rossby wave source (RWS) in the upper troposphere plays an important role in the tropical‐extratropical teleconnections. Using the daily outputs from the Phase 5 of the Coupled Model Intercomparison Project (CMIP5) models, the overall model performances in simulating the climatological Rossby wave sources in both winter and summer are evaluated. The ensemble mean of the CMIP5 models can simulate the large‐scale geographical distributions of the RWS reasonably close to the observations, with the simulations of RWS in general better in the Southern Hemisphere. For the Northern Hemisphere, most models overestimate the subtropical RWS but underestimate the midlatitude RWS in both winter and summer. Many models even fail to simulate the seasonal source‐sink shift of RWS in East Asia. Greatest intermodel differences are shown in East Asia, western North America in both seasons, and in the subtropical belt in winter hemisphere. Possible reasons for the model biases in RWS are further investigated. In the Northern Hemisphere, our analysis shows that model performance in simulating the local divergence, which might relate to the overly smoothed topography in Asia and western North America in the model, is most responsible for the biases of the RWS simulations. In the Southern Hemisphere, the bias in subtropical divergence pattern and tropical convection all contribute to the intermodel divergence of RWS simulation.